Hand hygiene knowledge, perception, and self-reported performance among nurses in Kelantan, Malaysia: a cross-sectional study - Mohamad Hazni Abd Rahim; Mohd Ismail Ibrahim (BMC, 2022)
Abstract Background Nurses interact with patients 24 hours a day, and this connection has the potential to raise the risk of infection transmission to patients. Nursing plays a vital role in pre-venting healthcare-associated infections (HCAIs) by ensuring that hand hygiene (HH) practises are followed and maintained. The purpose of this study was to evaluate nurses' knowledge, perceptions, and self-reported HH performance scores, as well as their correlation, in tertiary care hospitals in Kelantan, Malaysia. Methods A cross-sectional study was undertaken in all four Kelantan tertiary care hospitals from December 2019 to February 2020. A stratified random selection method was used to obtain a sample of 438 registered nurses. A validated WHO self-administered HH knowledge and perception questionnaire for healthcare personnel was used to measure HH knowledge, perception, and self-reported HH performance. Results The mean (SD) score of knowledge was 15.08 (1.96) out of the total 25. The score of perception participants towards HH was 68.02 (10.14) out of the total 81 and the average self-reported HH performance was 87.58 (12.03) out of 100. Pearson's correlation analysis showed significant positive correlations between perception and knowledge scores; r (436) =0.17, p<0.001 and Perception and self-reported HH performance scores; r (436) =0.27, p<0.001. Conclusions There is a strong link between knowledge and perception scores. Lack of understanding of HH during patient care might lead to a negative perception, which can affect overall self-reported HH performance. The need of monitoring and maintaining HH knowledge among nurses was established in this study.